Tardive Dyskinesia and Tardive Dystonia With Second-Generation Antipsychotics in Non-Elderly Schizophrenic Patients Unexposed to First-Generation Antipsychotics: A Cross-Sectional and Retrospective Study. Issue 1 (February 2015) - Ryu, Seunghyong; Yoo, Jae Hyun; Kim, Joo Hyun; Choi, Ji Sun; Baek, Ji Hyun; Ha, Kyooseob; Kwon, Jun Soo; Hong, Kyung Sue
Abstract : Abstract: This study investigates the clinical nature, prevalence rates, and associated factors of second-generation antipsychotic (SGA)–related tardive dyskinesia and tardive dystonia. To date, these subjects have not been thoroughly investigated. The subjects were 80 non-elderly schizophrenic patients who received SGAs for more than 1 year without any previous exposure to first-generation antipsychotics. Multiple (≥2) direct assessments of movement symptoms were performed. Hospital records longer than 1 recent year describing any observed tardive movement symptoms were reviewed. A current or history of tardive dyskinesia and/or tardive dystonia associated with SGA was identified in 28 (35%) subjects. These patients were being treated with risperidone (n = 15), amisulpride, olanzapine, aripiprazole, ziprasidone, or clozapine at the time of the onset of the movement symptoms. Tardive dyskinesia was mostly in the orolingual area, and the most frequently observed tardive dystonia was torticollis. The median interval between the first exposure to the SGA and the movement syndrome onset was 15 months for tardive dyskinesia and 43 months for tardive dystonia. A history of acute dystonia was significantly associated with tardive dystonia, and comorbid obsessive-compulsive syndrome was related to both tardive movement syndromes. This study indicates that more clinical attention and research efforts are needed regarding SGA-associated tardive movement syndromes, including a larger-scale prevalence assessment. This study is the first to indicate that a comorbid obsessive-compulsive syndrome might be an associated factor of tardive movement syndrome. The association warrants further investigation.